Estudio Para la Implementación de un Sistema de Gestión de Riesgos de Equipos Informáticos para la Universidad Técnica de Babahoyo. - Quiñonez Palma, Jorge Luis (2017)
In recent years several hardware "Hardware" has been infringed which has led to those in charge of managing the physical part of the computer equipment, to see how they can control this situation, to provide solutions in order to prevent the loss of information. One of the main shortcomings that are presented at the Technical University of Babahoyo are the weaknesses that are shown in certain laboratories, where students take certain pieces embedded in the computer as a hard disk, which can be very risky, it may contain information that is confidential and can be used for purposes that violate the state of information integrity processes, through the research carried out it was observed that the above mentioned process is of vital importance. In order to study the risks of computer equipment, it is necessary to analyze the internal processes of the teams and, in turn, analyze the context in which they are providing services and see how the bases can be reached, for the analysis of the reasons for the vulnerability of the subtraction of the physical devices of the equipment, it is necessary and of vital interest to take measures that lead to a prudent and effective solution, so it is of great importance maintain good control so that users can not violate hardware that is a significant asset within the institution.